The quarrel of development experts : Lauchlin Currie and Albert O. Hirschman in Colombia (2017)
Lauchlin Currie and Albert O. Hirschman worked together as advisers to the National Planning Council in Colombia in the 1950's. Both had little experience in development economics when they arrived, and did not see eye to eye about the functioning and policy recommendations of the Council. Retracing their debates on internal and public issues allows showing how the Colombian experience marked their views on the role of policy advisers, development policy and the obstacles to development processes. Our main contribution is to show how this experience contributed to enrich their theories of development. They evolved from the technical discussions on growth mechanics to the necessity to adopt a development strategy dealing with political-economy issues.